PKM Diversifikasi Produk Kuliner Berbahan Dasar Olahan Dari Buah Durian Di Desa Batetangnga Melalui Kegiatan PKM: Diversifikasi Produk Kuliner Berbahan Dasar Olahan Dari Buah Durian Di Desa Batetangnga Melalui Kegiatan PKM - Nasrah Natsir; Imran; Ahmad Syawaluddin; Nurhijrah; Maya Sari Wahyuni (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2024)
. This outreach to the community was carried out in Kanang, Batetannga Village, Binuang District, Polewali Mandar Regency, because most of the population there still depends on forest and agricultural products even though there is potential income from tourism and culinary businesses. This activity aims to train Kanang residents of Batetannga Village to diversify typical culinary products that can become the village's identity and tourist attraction. Village communities are also given cooking equipment to support entrepreneurial activities in the culinary sector. Product diversification with processed basic ingredients from durian fruit was chosen because durian is one of the mainstay commodities in Kanang, Batetannga Village. Durian fruit from the Kanang area of ​​Batetannga village is used as the main ingredient in making Durian Pie and Durian Pancakes. The training method is structured in several stages; (1) initial survey to determine the potential of culinary products, (2) planning and testing recipes, (3) creating standard recipes, (4) implementation, and (5) evaluation. The results of this activity are to help the Batetannga village community in producing culinary products typical of the Kanang region of Batetannga village, increasing product competitiveness (in terms of quality, quantity, added value, service and product diversification), as well as introducing the application of multimedia technology to promote and sell products. . The evaluation was carried out after training, and the diversification of durian products from the Kanang area of ​​Batetanngga village was marketed at food stalls in the Kanang tourist area, Batetannga Village.